Cortical oscillations and entrainment in speech processing during working memory load. (16th February 2018) - Hjortkjær, Jens; Märcher‐Rørsted, Jonatan; Fuglsang, Søren A.; Dau, Torsten
Abstract: Neuronal oscillations are thought to play an important role in working memory (WM) and speech processing. Listening to speech in real‐life situations is often cognitively demanding but it is unknown whether WM load influences how auditory cortical activity synchronizes to speech features. Here, we developed an auditory n‐back paradigm to investigate cortical entrainment to speech envelope fluctuations under different degrees of WM load. We measured the electroencephalogram, pupil dilations and behavioural performance from 22 subjects listening to continuous speech with an embedded n‐back task. The speech stimuli consisted of long spoken number sequences created to match natural speech in terms of sentence intonation, syllabic rate and phonetic content. To burden different WM functions during speech processing, listeners performed an n‐back task on the speech sequences in different levels of background noise. Increasing WM load at higher n‐back levels was associated with a decrease in posterior alpha power as well as increased pupil dilations. Frontal theta power increased at the start of the trial and increased additionally with higher n‐back level. The observed alpha–theta power changes are consistent with visual n‐back paradigms suggesting general oscillatory correlates of WM processing load. Speech entrainment was measured as a linear mapping between the envelope of the speech signal and low‐frequency cortical activity (< 13 Hz). We found that increases in both types of WM load (background noise and n‐back level) decreased cortical speech envelope entrainment. Although entrainment persisted under high load, our results suggest a top‐down influence of WM processing on cortical speech entrainment. Abstract : We used an auditory n‐back task to asses the effect of working memory (WM) load on cortical speech entrainment. Consistent with visual n‐back tasks, posterior alpha band power (8–13 Hz) decreased while frontal theta power (4–7 Hz) increased with WM load. At the same time, auditory cortical entrainment (< 13 Hz) to the envelope of the n‐back speech stimulus was found to decrease both with load level and with acoustic noise interference.